Failure Analysis of Composite Laminates Under Biaxial Tensile Load Due To Variations in Lamination Scheme / Mohamad Mali ... [et al.] - Mali, Mohamad; Samsudin, Azizul Hakim; Mahmud, Jamaluddin; Hussain, Ahmad Kamil (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Due to its variability in mechanical properties and complex anisotropy behaviour, the work related to the design and analysis of composite laminates or composite structures is complicated yet crucial. At present, the analytical and finite element simulation techniques are the more preferred methods than the tedious and costly physical testing procedures. Unfortunately, even after many research works have been conducted, there is still a lack of understanding in relation to the failure behaviour of composite laminates under the effect of biaxial load. This paper investigates the failure behaviour of fibre-reinforced composite laminates under biaxial tensile load due to variations in lamination scheme by comparing results obtained from analytical approach and finite element simulation. Failures in the laminates follow Maximum stress and Tsai-Wu criteria based on FSDT. The analytical approach was developed based on the CLT in which the computed strains, global stresses, principal stresses and displacements were used to predict the failure. The results from the finite element models were validated by comparing with the accepted published results. Three variations of lamination scheme; symmetric unidirectional-ply, cross-ply and angle-ply ([0/0]s & [90/90]s, [0/90]s and [+45/-45]s) were investigated. Comparison of the results obtained from the analytical and FEM were found in good agreement for all three schemes. In addition, it was found that the lamination scheme affected the failure behaviour composite laminates under the biaxial load. In conclusion, it can be concluded that the present study is useful and significant in enhancing knowledge about failure behaviour of composite laminates under biaxial tensile load.